Perencanaan Investasi Hijau pada Usaha Menengah Besar di Provinsi Jawa Tengah - Setiawan, Avi Budi; Pangestika, Maulida Dewi; Kusuma, Putri Patria; Yusuf, Mochammad (UI Scholars Hub, 2025)
This study aims to analyze green investment planning in medium and large enterprises in Central Java Province. This study employs several analytical tools, including regression with quadratic variables, Klassen Typology Analysis, and Analytic Network Process (ANP). The research locus is 35 districts/cities in Central Java Province. The results of the study show that industries in Central Java contribute significantly to economic transformation, but also harm environmental quality, the regression results show the Pollution Haven Hypothesis in several main industries in Central Java. The sectors that have potential to reduce the quality of the environment are oil and gas mining, textiles, leather goods, and transportation, so incoming investment needs to be directed to reduce negative externalities that arise.